Safe production of farmed Atlantic salmon (Salmo salar) - Dahle, Stine Veronica Wiborg; Westavik, Harry; Sandberg, Merete Gisvold; Garforth, Dave; Winkel, Clare; Andree, Sabine; Martinez, Iciar (SINTEF Fiskeri og havbruk, 2010)
This work contains a review of the undesirable substances that may be introduced as contaminants of natural and malicious origin, and of emerging hazards, in the production chain of farmed salmon,from ova to packed fillet. The work, focused in the supply chain to European countries, contains a brief introduction to general food safety in relation to aquaculture products, followed by an overview of the Production chain for salmon with indication of where in the chain the undesirable substances might be introduced. The review ends with the outlining of best manufacturing practices, the identification of emerging risks and the application of the failure mode effects analysis methodology to the identification of the steps, in the entire production chain, vulnerable to contamination.